Aerobic Fitness Level of Class VIII Students Reviewed from VO2MAX - Muwardi Binanto Raharjo; Jariono, Gatot; Warthadi, Anugrah Nur (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This research aims toto determine the level of aerobic fitness of students at SMP Negeri 3 Karangdowo, especially class VIII students, in this study the researcher used a quantitative research type, the method used in this study was a survey and used a data collection technique in the form of an aerobic endurance test using a bleep test run. This study sample consisted of 20 students, 10 male students and 10 female students. The sampling technique in this study used purposive sampling. There are several categories of girls or boys in this study, including very low, low, sufficient, good, very good. The results of this study In the results of this study it can be seen that the level of aerobic fitness of male students who have a very low VO2 Max category is 0 students if presented 0%, students who have a low category are 3 if presented 30%, students who have a sufficient category are 6 if presented 60%, students who have a good category are 1 if presented 10%. Meanwhile, the results of the study on the level of aerobic fitness of female students who have a very low category are 1 if presented at 10%, students who have a low category are 5 if presented at 50%, students who have a sufficient category are 4 if presented at 40%, students who have a good category are 0 if presented at 0%, students who have a very good category are 0 if presented at 0%.